ECG monitoring on swimming endurance and heart rate of jack mackerel Trachurus japonicus during repeated exercise - Nofrizal (2019)
The swimming performance of jack mackerel after post-exercise recovery was evaluated through electrocardiograph (ECG) monitoring. Jack mackerels were forced to swim in the flume tank, with the swimming speed levels of 1.09-9.12 fork length per second (FL˙sˉ¹) at 15C and 22C. Firstly, the heart rate was monitored in still water as a control, and continuously to observe the heart rate during exercise for 200 minor until fatigue as the 1st exercise trial. The post-exercise recovery was observed after stopping the flow as the 1st recovery phase. Secondly, after confirming the complete recovery of fish monitored by ECG, the same fish was again forced to swim as the 2nd exercise trial. The heart rate activity was also continuously observed in the 2nd recovery phase. The swimming endurance and heart rate patterns were the same between the 1st and 2nd exercise at respective swimming speed level for 15C and 22C. It is therefore suggested that previous capture of fish by an active fishing gear involving swimming and exhaustion may not have an impact on its ability to respond to the gear in the subsequent encounter if the fish is able to get complete recovery from the previous encounter.